الدعوى الجمركية: دراسة تحليلية في ضوء النظام السعودي (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2024)
This study aims to shed light on the Saudi legal system governing customs lawsuits in terms of their formal and substantive conditions and the judicial bodies competent to consider customs lawsuits. The study adopted an analytical approach to the provisions of the Gulf Cooperation Council (GCC) law, related regulations, and the decisions of customs committees. The study is divided into two sections: the first discusses the initiation of customs lawsuits, and the second addresses the court competent to consider customs lawsuits. The study concluded with several findings and recommendations, the most important of which are as follows:1.  The formal conditions for initiating a customs lawsuit include submitting a written request from the Director General of Customs, the Zakat, Tax, and Customs Authority (the Authority), and including sufficient data in the request. The substantive conditions include the issuance of the request by the legally authorized person and directing the request to the Public Prosecution.2.  Customs lawsuits are considered by three primary judicial committees, supervised by the Secretariat of Zakat, Tax, and Customs Committees. The decisions of the primary committees can be appealed before the Appeals Committee in Riyadh.3.  The customs committees are competent to consider customs smuggling crimes stipulated in Articles 142 and 143 of the Unified Customs Law. They also have jurisdiction over violations against the executive regulations of the mentioned system, as well as objections to collection and fine decisions covered by Articles 147 and 148 of the system.4.  The criterion governing the jurisdiction to initiate a customs lawsuit is the date of the goods' import declaration or export date. If the declaration date is before 02/09/1440 AH, the jurisdiction lies with the Authority. If the declaration is issued after 02/09/1440 AH, the jurisdiction lies with the Public Prosecution.5.  We recommend researchers and students conduct their research in Saudi customs and tax law, focusing on types of crimes and violations, their penalties, and the statute of limitations in customs and tax matters. They should consider Algerian law as a comparative law due to its recent amendments, the latest of which was in 2017.
Keywords: جمارك; دعوى; شروط; النيابة; نظام الجمارك الموحد; اللجان; التهريب; جرائم; مخالفات